Room-temperature quasi-catalytic hydrogen generation from waste and water - Wu, Hongguo; Zhang, Li-Long; Wang, Junqi; Jiang, Yiyuan; Li, Hu; Sudarsanam, Putla; Yang, Song (Green Chemistry, 2021)
A solvation-driven catalyst-free H-2 generation system from water and various waste hydrosilanes at room temperature was developed, with good to quantitative H-2 yields in minutes. Using a green solvent is found to promote the strong coordination of proton carriers with hydrosilane to liberate H-2 based on molecular dynamics simulations. Theoretical calculations clarify that OH(-)in situ generated from H2O enabled by solvation is favorable for activating the Si-H species of hydrosilane, and the in situ formed Si-OH interacts more effectively with the adjacent remaining Si-H, both contributing to the overall enhanced H-2 generation. Moreover, the overall life-cycle impacts of the developed system are less than those of industrial H-2 production processes, especially in ozone layer depletion and abiotic depletion resources - fossil fuels. This protocol realizes the potential of efficiently producing H-2 from waste and water, and opens a new avenue to alleviate petroleum consumption.